Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(=x+2\sqrt{xy}+y-9\)
\(=\left(\sqrt{x}+\sqrt{y}\right)^2-3^2\)
\(=\left(\sqrt{x}+\sqrt{y}-3\right)\left(\sqrt{x}+\sqrt{y}+3\right)\)
\(xy-y\sqrt{x}+\sqrt{x}-1\)
\(=y\left(x-\sqrt{x}\right)+\left(\sqrt{x}-1\right)\)
\(=y\sqrt{x}\left(\sqrt{x}-1\right)+\left(\sqrt{x}-1\right)\)
\(\left(\sqrt{x}-1\right)\left(y\sqrt{x}+1\right)\)
22222222222222222222222222222222222222222222222222222222222222222222222222222222222222222222222222222222222222222222222222222222222222222222222222222222222222222222222222222222222222222222222222222222222222222222222222222222222222222222222222222222222222222222222222222
a: \(=x-\sqrt{xy}+y-x+2\sqrt{xy}-y=\sqrt{xy}\)
b: \(=\dfrac{1+\sqrt{a}}{a-\sqrt{a}}\cdot\dfrac{\left(\sqrt{a}-1\right)^2}{\sqrt{a}+1}=\dfrac{\sqrt{a}-1}{\sqrt{a}}\)
a/ \(A=xy+y\sqrt{x}+\sqrt{x}+1\left(x\ge0\right)\)
\(=y\sqrt{x}\left(\sqrt{x}+1\right)+\sqrt{x}+1\)
\(=\left(\sqrt{x}+1\right)\left(y\sqrt{x}+1\right)\)
b/ \(B=x-3\sqrt{xy}+2y\left(x\ge0;y\ge0\right)\)
\(=x-\sqrt{xy}-2\sqrt{xy}+2y\)
\(=\sqrt{x}\left(\sqrt{x}-\sqrt{y}\right)-2\sqrt{y}\left(\sqrt{x}-\sqrt{y}\right)\)
\(=\left(\sqrt{x}-\sqrt{y}\right)\left(\sqrt{x}-2\sqrt{y}\right)\)
c/\(C=2a-7\sqrt{ab}+5b\left(x\ge0;y\ge0\right)\)
\(=2a-2\sqrt{ab}-5\sqrt{ab}+5b\)
\(=2\sqrt{a}\left(\sqrt{a}-\sqrt{b}\right)-5\sqrt{b}\left(\sqrt{a}-\sqrt{b}\right)\)
\(=\left(\sqrt{a}-\sqrt{b}\right)\left(2\sqrt{a}-5\sqrt{b}\right)\)
Thôi không cần nữa